2018
DOI: 10.3758/s13423-018-1506-x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical error monitoring

Abstract: Error monitoring has recently been discovered to have informationally rich foundations in the timing domain. Based on the common properties of magnitude-based representations, we hypothesized that judgments on the direction and the magnitude of errors would also reflect their objective counterparts in the numerosity domain. In two experiments, we presented fast sequences of "beeps" with random interstimulus intervals and asked participants to stop the sequence when they thought the target count (7, 11, or 19) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Our findings showed that in the absence of explicit feedback, humans can monitor the direction of errors in their reproductions of lengths (for nearly all targets) and their confidence ratings can track the magnitude of their errors for all target lengths. Together with our previous findings which indicate that humans can better than chance guess the direction and match their confidence to the degree of errors (based on composite measure) in their temporal (Akdoğan & Balcı, 2017; see also Doenyas, Mutluer, Genç, & Balcı, 2019;Kononowicz et al, 2018) and numerical (Duyan & Balcı, 2018) reproductions and numerical estimations (Duyan & Balcı, 2019), the results of Samaha and Postle (2017) that point toward a similar ability in relation to orientation judgment errors, and given converging evidence for a general magnitude representation system in the brain (Bueti & Walsh, 2009;Walsh, 2003), we surmise that this error monitoring ability would most likely extend to other metric domains.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our findings showed that in the absence of explicit feedback, humans can monitor the direction of errors in their reproductions of lengths (for nearly all targets) and their confidence ratings can track the magnitude of their errors for all target lengths. Together with our previous findings which indicate that humans can better than chance guess the direction and match their confidence to the degree of errors (based on composite measure) in their temporal (Akdoğan & Balcı, 2017; see also Doenyas, Mutluer, Genç, & Balcı, 2019;Kononowicz et al, 2018) and numerical (Duyan & Balcı, 2018) reproductions and numerical estimations (Duyan & Balcı, 2019), the results of Samaha and Postle (2017) that point toward a similar ability in relation to orientation judgment errors, and given converging evidence for a general magnitude representation system in the brain (Bueti & Walsh, 2009;Walsh, 2003), we surmise that this error monitoring ability would most likely extend to other metric domains.…”
Section: Discussionsupporting
confidence: 86%
“…In such an in-parallel information processing scheme, participants can compare their estimate to the other estimate(s) that would have been made if they had relied on another process/other processes in a retrospective fashion and this comparison can inform the agent regarding the direction and magnitude of their errors. Duyan and Balcı (2018) proposed another comparison strategy in which participants would compare their current estimate of magnitude with a random sample from their long-term memory representation for that target. In fact, such a comparison strategy forms the basis of the decision stage of the Scalar Timing Theory to guide the first order timing performance (Gibbon, Church, & Meck, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such performance monitoring is an important component of metacognition [Fleming & Dolan, ; Garofalo & Lester, ], which in decision‐making comprises both veridical error‐monitoring and confidence judgments regarding objective performance in the absence of explicit feedback [Yeung & Summerfield, ]. Importantly, recent work has shown that typically developing (TD) individuals are aware of not only their errors but also the magnitude and direction of their errors in paradigms that enable such quantitative characterizations [Akdoğan & Balcı, ; Duyan & Balcı, ]. In the present study, we combined decision‐making, timing, and error‐monitoring, which have remained as segregated research topics in ASD up until now, to take a more comprehensive approach to understanding cognitive processing in ASD in the light of recent developments in the corresponding fields.…”
Section: Introductionmentioning
confidence: 99%